Polychaetes (Annelida: Polychaeta) off Kıyıköy (Black Sea, Türkiye) with descriptions of three new species - Çinar, Melih Ertan; Erdoğan-Dereli̇, Deniz (Zootaxa, 2023)
The examination of benthic materials collected in September 2022 at six stations off Kıyıköy (south-west coast of the Black Sea, Türkiye) both on hard (three stations) and soft substrata (three stations) at depths ranging from 8 and 27 m revealed a total of 57 polychaete species belonging to 22 families. Among the species, the polynoid Malmgrenia polypapillata is a new record for the Black Sea fauna, and three species belonging to the Syllidae (Erinaceusyllis defneae n. sp.) and Terebellidae (Polycirrus karadenizicus n. sp. and P. rhombolabiatus n. sp.) are new to science. Algae dominated (Cystoseira cinita, Cladophora sp. and Phyllophora crispa) rocky substrata had 30 polychaete species and a maximum polychaete density of 7325 individuals/m2, while soft bottom substrata (fine sand and muddy sand with shell fragments) possessed 38 species and a maximum polychaete density of 3520 individuals/m2. The family Nereididae (31–76% of the total number of individuals), and the species Platynereis dumerilii and Polyphthalmus pictus dominated hard bottom stations, whereas the families Nephtyidae, Spionidae and Dorvilleidae, and the species Micronephthys longicornis, Protodorvillea kefersteini and Prionospio maciolekae were represented by high number of individuals at soft-bottom stations.